IMPLEMENTATION OF AS-SULUH AS AN ALTERNATIVE SHARIA BUSINESS DISPUTE RESOLUTION IN INDONESIAN LEGISLATION - M. Arif Al Kausari; Jaya Miharja (Mu'amalat: Jurnal Kajian Hukum Ekonomi Syariah, 2024)
This research aims to explain the application of the as-sulh concept contained in the study of Islamic law in the form of sharia business dispute resolution in accordance with the context of existing laws and regulations in Indonesia. The research method used in this research is normative-descriptive with a statute approach. The findings of this research are that the as-sulh principle emphasizes the principle of peace carried out in a wider scope, both in terms of politics, family and business relations. Meanwhile, in the legal system in Indonesia, the concept of as-sulh is known in the form of alternative dispute resolution (ADR) in the form of consultation, negotiation, mediation, reconciliation and expert opinion with characteristics that are different from each other.